Applying to college: Do information deficits lower the likelihood of college-eligible students from less-privileged families to pursue their college intentions?: Evidence from a field experiment - Martin Ehlert; Claudia Finger; Alessandra Rusconi; Heike Solga (Social Science Research, 2017)
Information deficits are considered an important source of why students from less-privileged families do not enroll in college, even when they are college-eligible and intend to go to college. In this paper, we examine whether correct and detailed information on the costs of and returns to higher education increases the likelihood of college applications of less-privileged high school graduates who expressed college intentions in their junior high school year. We employ an experimental design with a randomly assigned 25-minute information treatment about funding opportunities for, and returns to, higher education given at Berlin schools awarding university entrance qualifications. Our analyses show that our information treatment indeed substantially increases the likelihood of treated less-privileged students to apply to college. Our study indicates that our low-cost provision of financial information not only increased their college knowledge but also substantially changed their college application behavior, despite other existing barriers, like economic constraints.
Keywords: 330; information; educational decisions; educational inequality; college application; rational choice; field experiment